Arabidopsis wat1 (walls are thin1)‐mediated resistance to the bacterial vascular pathogen, Ralstonia solanacearum, is accompanied by cross‐regulation of salicylic acid and tryptophan metabolism. (26th November 2012) - Denancé, Nicolas; Ranocha, Philippe; Oria, Nicolas; Barlet, Xavier; Rivière, Marie‐Pierre; Yadeta, Koste A.; Hoffmann, Laurent; Perreau, François; Clément, Gilles; Maia‐Grondard, Alessandra; van den Berg, Grardy C.M.; Savelli, Bruno; et al.
Summary: Inactivation of Arabidopsis WAT1 ( Walls Are Thin1 ), a gene required for secondary cell‐wall deposition, conferred broad‐spectrum resistance to vascular pathogens, including the bacteria Ralstonia solanacearum and Xanthomonas campestris pv. campestris, and the fungi Verticillium dahliae and Verticillium albo‐atrum . Introduction of NahG, the bacterial salicylic acid (SA)‐degrading salicylate hydroxylase gene, into the wat1 mutant restored full susceptibility to both R. solanacearum and X. campestris pv. campestris . Moreover, SA content was constitutively higher in wat1 roots, further supporting a role for SA in wat1 ‐mediated resistance to vascular pathogens. By combining transcriptomic and metabolomic data, we demonstrated a general repression of indole metabolism in wat1‐1 roots as shown by constitutive down‐regulation of several genes encoding proteins of the indole glucosinolate biosynthetic pathway and reduced amounts of tryptophan (Trp), indole‐3‐acetic acid and neoglucobrassicin, the major form of indole glucosinolate in roots. Furthermore, the susceptibility of the wat1 mutant to R. solanacearum was partially restored when crossed with either the trp5 mutant, an over‐accumulator of Trp, or Pro35S:AFB1‐myc, in which indole‐3‐acetic acid signaling is constitutively activated. Our original hypothesis placed cell‐wall modifications at the heart of the wat1 resistance phenotype. However, the results presented here suggest a mechanism involving root‐localized metabolic channeling away from indole metabolites to SA as a central feature of wat1 resistance to R. solanacearum .